2017
DOI: 10.1111/cas.13278
|View full text |Cite
|
Sign up to set email alerts
|

Phase I clinical trial of cell division associated 1 (CDCA1) peptide vaccination for castration resistant prostate cancer

Abstract: Cell division associated 1 (CDCA1) was screened as an oncogene that is overexpressed on several cancers, including prostate cancer. A highly immunogenic HLA‐A*2402‐restricted epitope peptide corresponding to part of the CDCA1 protein was also identified. A phase I clinical trial was conducted for patients with castration resistant prostate cancer (CRPC) using a CDCA1 peptide vaccination. Twelve patients having HLA‐A*2402 with CRPC after failure of docetaxel chemotherapy were enrolled. They received subcutaneou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 30 publications
0
31
0
Order By: Relevance
“…We screened and identified an HLA‐A*2402‐restricted epitope peptide, CDCA1‐A24‐56‐64, that has a high antigenic activity to induce CTL . Recently, we reported a phase I clinical trial for patients with CRPC using a CDCA1 peptide vaccination . Twelve patients having HLA‐A*2402 with CRPC after failure of docetaxel chemotherapy were enrolled.…”
Section: Prostate Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…We screened and identified an HLA‐A*2402‐restricted epitope peptide, CDCA1‐A24‐56‐64, that has a high antigenic activity to induce CTL . Recently, we reported a phase I clinical trial for patients with CRPC using a CDCA1 peptide vaccination . Twelve patients having HLA‐A*2402 with CRPC after failure of docetaxel chemotherapy were enrolled.…”
Section: Prostate Cancermentioning
confidence: 99%
“…29 Recently, we reported a phase I clinical trial for patients with CRPC using a CDCA1 peptide vaccination. 4 RCC until approval of molecular-targeted medicines. Recently, nivolumab (anti-PD-1) showed an OS benefit in patients previously treated with TKI for metastatic RCC, which led to approval.…”
Section: F I G U R Ementioning
confidence: 99%
“…NUF2 is a composition of a molecular linker between the kinetochore attachment site and the tubulin subunits within the lattice of the attached plus ends [19]. NUF2 is also an oncogene that is over-expressed on several cancers [5,20], including lung adenocarcinoma. Comparing with previous study, the NUF2 expression in multiple databases was signi cantly higher than in normal tissues, and also signi cantly higher in LUAD and LUSC [7].…”
Section: Discussionmentioning
confidence: 99%
“…42,43 To evaluate the risk of autoimmunity induction by overexpressed self-antigen-derived peptide vaccinations, several preclinical and clinical trials have demonstrated that peptides derived from overexpressed self-antigens were able to induce effective and specific CTL responses without any serious systemic adverse events. [44][45][46][47] However, studies by Overwijk and Restifo 48 and Overwijk et al 49 revealed that potent CD8 + T-cell responses induced with MDA in melanoma patients could interact with melanocytes in the skin, resulting in autoimmune depigmentation. Therefore, if hPEBP4-derived peptides are to serve as candidates for CTL-based immunotherapy against breast cancer or other hPEBP4-expressing carcinomas, their safety and tolerability need to be further assessed in basic and clinical studies.…”
Section: Discussionmentioning
confidence: 99%